Crystal growth and scintillation properties of tube shape-controlled Ce-doped Y3Al5O12 single crystals grown by micro-pulling-down method. (23rd November 2020) - Kotaki, Atsushi; Yoshino, Masao; Yokota, Yuui; Hanada, Takashi; Yamaji, Akihiro; Toyoda, Satoshi; Sato, Hiroki; Ohashi, Yuji; Kurosawa, Shunsuke; Kamada, Kei; Yoshikawa, Akira
Abstract: Tube shape-controlled Ce-doped Y3 Al5 O12 (tube-Ce:YAG) single-crystal scintillators were directly grown from a melt via the micro-pulling-down method using a specially-designed iridium crucible. Back-scattering Laue images and X-ray diffraction measurements revealed the tube-Ce:YAG was a single crystal with the YAG phase. Ce distribution in the tangential direction of the tube-Ce:YAG specimen showed that Ce concentrations around the capillary positions were lower than at the corners. This was caused by the small Ce segregation coefficient in the YAG single crystal and from the small convection in the meniscus. The scintillation properties of tube-Ce:YAG specimens were comparable with previously reported Ce:YAG single crystals.